2021
DOI: 10.1007/s00429-021-02281-0
|View full text |Cite
|
Sign up to set email alerts
|

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping

Abstract: Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The interrater reliability was calculated based on eight stroke lesion masks using the same method as for the tumor interrater reliability. The interrater reliability for all three raters was 81.3 % (range 69.8–91.1 %), as reported previously ( Lugtmeijer et al, 2021 ).…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The interrater reliability was calculated based on eight stroke lesion masks using the same method as for the tumor interrater reliability. The interrater reliability for all three raters was 81.3 % (range 69.8–91.1 %), as reported previously ( Lugtmeijer et al, 2021 ).…”
Section: Methodssupporting
confidence: 84%
“…The aim of this study is to investigate if brain areas where both stroke and tumor populations have adequate coverage, show topographical overlap in lesion-symptom associations. For this study, data from two different studies were combined: a single-center retrospective study in a cohort of treatment-naïve diffuse glioma patients ( van Kessel et al, 2019 , van Kessel et al, 2022 ) and a multi-center prospective cohort study in patients with ischemic stroke ( Lugtmeijer et al, 2021 , Lammers et al, 2022 ). With a state-of-the-art machine learning-based, multivariate voxel-wise approach, we produced lesion-symptom maps for memory and verbal fluency tasks for both populations separately.…”
Section: Introductionmentioning
confidence: 99%
“…Lesion mapping studies have suggested distinct associations between lesion location and working or episodic memory deficits after stroke. 2 A similar dissociation could apply to cognitive recovery, through domain and network-specific mechanisms of plasticity and neural adaptation. Generic mechanisms may also operate that support recovery across multiple domains.…”
Section: Introductionmentioning
confidence: 96%
“…Working memory, the ability to temporarily maintain and mentally manipulate information, is fundamental to cognition (Baddeley, 1986 ). This ability is known to require communication and neuronal processing across distributed brain regions and is conserved over mammalia (Goldman-Rakic, 1991 ;Sarnthein et al, 1998 ;Lee and Kesner, 2003 ;Winter and Stich, 2005 ;Wang and Cai, 2006 ;Eichenbaum, 2008 ;Fell and Axmacher, 2011 ;Christophel et al, 2017 ;Eichenbaum, 2017 ;Churchwell and Kesner, 2011 ;Spellman et al, 2015 ;Hallock et al, 2016 ;Ito et al, 2015 ;Bolkan et al, 2017 ;Ito et al, 2018 ;Maisson et al, 2018 ;Lugtmeijer et al, 2021 ). Long-range interactions are thought to be supported by the proper timing of action potentials (spikes), and brain rhythms are thought to act as a clocking mechanism to synchronize the timing of spike discharges (Fries, 2005 ;Buzsaki, 2006 ;Fell and Axmacher, 2011 ;Colgin, 2011 ;Fries, 2015 ).…”
Section: Introductionmentioning
confidence: 99%